The Prophetic Model in Language Learning: An Approach of Arabic Dialogue Material - Eka Lutfiyatun; Muhamad Harun; Depi Kurniati; M. Rizky Ramadhan; Gita Marga Reza; Ghina Maysya Ayu (JPI: Jurnal Pustaka Indonesia, 2026)
Challenges in Islamic education related to students' competencies and character development remain a concern. One such case is observed at SMP Plus Islam Al-Fahd, where issues include limited oral communication skills in Arabic and the underdeveloped Islamic character. Despite being enrolled in an Islamic boarding school, students still require reinforcement in both spoken Arabic proficiency and Islamic values to ensure these competencies can be effectively applied in daily life. To address this, there is a need to develop supplementary materials aimed at optimizing Arabic speaking skills while integrating character education. This study aims to develop a companion book to enhance students' Arabic speaking skill, internalized with Islamic character values. The research adopts a Research and Development approach using the ADDIE model, encompassing the stages of Analyze, Design, Develop, Implement, and Evaluate. The outcome is a set of materials designed for practicing Arabic dialogues with contextual themes infused with Islamic character content. Overall, in terms of language, content, and design, the developed materials have been validated by experts as appropriate and are deemed ready for the next stages of implementation and potential large-scale publication. The Islamic values embedded in the dialogues are derived from the noble attributes of the Prophet Muhammad, which include honesty, intelligence, a sense of responsibility, and a commitment to sharing knowledge as foundation for character building.